Determining Death in Uncontrolled DCDD Organ Donors - Bernat, James L. (The Hastings Center report, 2013)
The most controversial issue in organ donation after the circulatory determination of death is whether the donor was truly dead at the moment death is declared. My colleagues and I further analyzed this issue by showing the relevance of the distinction between the “permanent” and the “irreversible” loss of circulatory functions. Permanent cessation means that circulatory function will not return because it will not be restored spontaneously and medical attempts to restore it will not be conducted. By contrast, irreversible cessation means that circulatory function cannot be restored using currently available technology. In this issue of the Report, Kevin Munjal and colleagues criticize the unjustified application of the permanent-irreversible distinction, which my colleagues and I developed for cDCDD, to their well-designed and carefully conducted experimental protocol of uncontrolled DCDD (uDCDD) in New York City, for which our analysis was not targeted. They claimed that to determine a donor's death in uDCDD, it is unnecessary to show that permanence is a valid surrogate indicator of irreversibility because the unsuccessful attempt to resuscitate the patient comprises prima facie evidence of circulatory irreversibility. Ironically, that potent justification defending death determination in uDCDD yields limitations that are similar to those created when our permanent-irreversible distinction is applied to death determination in cDCDD.